Hebb-Based Rules of Neural Plasticity: Are They Ubiquitously Important for the Refinement of Synaptic Connections in Development?. (February 2014) - Favero, Morgana; Cangiano, Alberto; Busetto, Giuseppe
Neuronal death and suppression of functional synaptic inputs are well-known regressive events characterizing PNS and CNS development. In the CNS, participation of activity in synapse elimination has been known ever since the pioneering studies of Hubel and Wiesel, but only recently has a Hebb-based mechanism of spike synchrony versus asynchrony received unequivocal experimental support in the visual system. At the neuromuscular junction (NMJ), where synapse elimination was discovered, the specific function of the "timing of activity" was addressed by only one group of studies and did not receive widespread attention. Here we critically review the latest NMJ investigation advocating an "activity-independent" mechanism for synapse elimination and contrast it with an equally recent study demonstrating a key role for spike timing. Finally, we highlight how the striking similarities between the two mentioned studies on spike timing (visual system and NMJ) establish conclusively its role in the development of the nervous system in general.